Distributed model reference control for synchronization of a vehicle platoon with limited output information and subject to periodical intermittent information - Prayitno, Agung; Indrawati, Veronica; Nilkhamhang, Itthisek (Zielona Góra: Uniwersytet Zielonogórski)
Vehicles involved in platoon formation may experience difficulties in obtaining full-state information that can be exchanged and used for controller synthesis. Therefore, a distributed controller based on a model reference and designed utilizing a cooperative observer is proposed for vehicle platoon synchronization. The proposed controller is composed of three main blocks, namely, the reference model, the cooperative observer and the main controller. The reference model is developed by using a homogeneous vehicle platoon that utilizes cooperative full-state information. The cooperative observer is a state estimator which is constructed based on the cooperative output estimation error. It provides state estimates to be used by the main controller.
Keywords: cooperative observer; distributed model reference control; intermittent information; vehicle platoon